2002
DOI: 10.1007/s00204-002-0372-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonylphenol on the antioxidant system in epididymal sperm of rats

Abstract: Nonylphenol, an environmental contaminant, has been shown to induce reproductive abnormalities in male rats. The nature and mechanism of action of nonylphenol on the epididymal sperm has not been elucidated. In the present study we have sought to investigate whether administration of nonylphenol induces oxidative stress in rat epididymal sperm. Nonylphenol was administered orally to male rats at 1, 10 and 100 microg/kg body weight per day for 45 days. Twenty-four hours after the last treatment, rats were weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(10 citation statements)
references
References 32 publications
3
6
1
Order By: Relevance
“…In concordance with our results, Wu et al showed significant decrease in the levels of GSH and SOD in BPA group; this decrease indicated liver tissues damage [29]. Similarly, in other organs ROS were induced when BPA was administered during the embryonic and infancy [11, 14, 30]. Similarly, others demonstrated that BPA generates ROS that causes oxidative damage in the brain, reproductive tract, and kidney of rats [5, 31, 32].…”
Section: Discussionsupporting
confidence: 90%
“…In concordance with our results, Wu et al showed significant decrease in the levels of GSH and SOD in BPA group; this decrease indicated liver tissues damage [29]. Similarly, in other organs ROS were induced when BPA was administered during the embryonic and infancy [11, 14, 30]. Similarly, others demonstrated that BPA generates ROS that causes oxidative damage in the brain, reproductive tract, and kidney of rats [5, 31, 32].…”
Section: Discussionsupporting
confidence: 90%
“…It has been valued that the human body is daily exposed to about 7.5 μg/day of nonylphenol (NP) (Lagos-Cabré and Moreno, 2012). In rodent models exposed to NP or OP, it has been shown a testicular damage with a decrease in the testicular size and weight, in the epididymis and sperm production, an increase of the intertubular space and low seminal quality Lee et al, 1999;Chitra et al, 2002;Herath et al, 2004;Lagos-Cabré and Moreno, 2012;Knez, 2013;Ponzo and Carbone, 2013). Moreover, NP exposure neonatally, in early stages of sexual maturation and in adulthood rat, led to a histological disorganization of the epithelium seminiferus of testis (Ponzo and Carbone, 2013), a reduction in testis, epididymis and seminal vesicle size other than an increase of cryptorchidism up to a 60% (Lee, 1998;Nagao et al, 2001;Fan et al, 2010;Ponzo and Carbone, 2013).…”
Section: Alkylphenolsmentioning
confidence: 99%
“…These compounds include phthalate esters,121,122 sulfur dioxide,123 sodium fluoride,124 a range of environmental estrogens (e.g., PCBs,2,39,125127 methoxychlor,128,129 bisphenol A130,131 nonylphenol132), chemotherapeutic agents (e.g., adriamycin,135 cisplatin136,137 cyclophosphamide138140) hexachlorocyclohexane,141142 2,4,6-trinitrotoluene,143 aflatoxin,144 lindane,145 quinalphos146 endosulfan,147 diethyl maleate,148 monensin,149 formaldehyde,150 alloxan,151,152 streptozotocin,86 acrylamide153 and ozone 154. In addition to this list of xenobiotic chemicals that can induce oxidative stress in the testes, physical factors such as static magnetic fields155 and electromagnetic radiation in its various forms from heat12,156 to X-ray157 irradiation, can also trigger a state of oxidative stress in testicular tissue.…”
Section: Disruption Of the Antioxidant Status Of The Testesmentioning
confidence: 99%